Bilateral pulmonary embolism after arthroscopic anterior cruciate ligament reconstruction: A case report - Koaban, Saeed (Int J Surg Case Rep, 2018)
INTRODUCTION: Venous thromboembolism is a serious complication in orthopedic surgery. It is very common in major surgery, such as total hip arthroplasty. However, few reports have described the incidence of pulmonary embolism and its associated risk factors following less invasive surgery, such as arthroscopic knee surgery. PRESENTATION OF CASE: We describe a rare presentation of a young man with bilateral pulmonary embolism of the main pulmonary arteries following arthroscopic anterior cruciate ligament reconstruction. DISCUSSION: The present patient is different from other similar cases in that he was an active healthy man without any risk factors for the development of thrombosis. Despite this, he experienced a bilateral pulmonary embolism one week after knee arthroscopy. CONCLUSION: Although anterior cruciate ligament reconstruction is a common and safe procedure performed on a daily basis, unexpected complications may occur. One of these is venous thromboembolism which may be fatal.